Applying multi‐omics toward tumor microbiome research. Issue 1 (9th January 2023) - Zhang, Nan; Kandalai, Shruthi; Zhou, Xiaozhuang; Hossain, Farzana; Zheng, Qingfei
Abstract: Rather than a "short‐term tenant, " the tumor microbiome has been shown to play a vital role as a "permanent resident, " affecting carcinogenesis, cancer development, metastasis, and cancer therapies. As the tumor microbiome has great potential to become a target for the early diagnosis and treatment of cancer, recent research on the relevance of the tumor microbiota has attracted a wide range of attention from various scientific fields, resulting in remarkable progress that benefits from the development of interdisciplinary technologies. However, there are still a great variety of challenges in this emerging area, such as the low biomass of intratumoral bacteria and unculturable character of some microbial species. Due to the complexity of tumor microbiome research (e.g., the heterogeneity of tumor microenvironment), new methods with high spatial and temporal resolution are urgently needed. Among these developing methods, multi‐omics technologies (combinations of genomics, transcriptomics, proteomics, and metabolomics) are powerful approaches that can facilitate the understanding of the tumor microbiome on different levels of the central dogma. Therefore, multi‐omics (especially single‐cell omics) will make enormous impacts on the future studies of the interplay between microbes and tumor microenvironment. In this review, we have systematically summarized the advances in multi‐omics and their existing and potential applications in tumor microbiome research, thus providing an omics toolbox for investigators to reference in the future. Abstract : In this review, we have systematically summarized the advances of multi‐omics and their existing and potential applications in tumor microbiome research, thus providing an omics toolbox for investigators to reference in the future. Highlights: The tumor microbiome plays a significant role in carcinogenesis, cancer development, metastasis, and cancer therapies. The tumor microbiome has great potential to become a target for early diagnosis and treatment of cancer. Genomics, transcriptomics, proteomics, and metabolomics are powerful approaches for tumor microbiome studies, by facilitating an understanding of different levels of the central dogma. Multi‐omics will make enormous impacts on future research of the tumor microbiome. The development of single‐cell multi‐omics technologies will motivate the progression of the tumor microbiome field.